1995
DOI: 10.1007/bf00690293
|View full text |Cite
|
Sign up to set email alerts
|

The ?6?1 and ?6?4 integrins in human prostate cancer progression

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Washington Headquarters Services, Directorate for Information Operations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
156
0
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 181 publications
(170 citation statements)
references
References 51 publications
12
156
0
2
Order By: Relevance
“…Loss of the 6 4 integrin may give a less-stable attachment to the ECM, while the continued expression of the 6 1 integrin may provide enough attachment for the cells to become mobile. This may also explain why prostate cancer cells favor to move along laminin-5 coated nerves (Cress et al 1995).…”
Section: Integrinsmentioning
confidence: 99%
“…Loss of the 6 4 integrin may give a less-stable attachment to the ECM, while the continued expression of the 6 1 integrin may provide enough attachment for the cells to become mobile. This may also explain why prostate cancer cells favor to move along laminin-5 coated nerves (Cress et al 1995).…”
Section: Integrinsmentioning
confidence: 99%
“…Changes in several adhesion and motility associated proteins have been identified. Differential expression of transmembrane integrin receptor subtypes, in prostate cancer as compared to normal prostate, has been reported by a number of investigators (Cress et al, 1995;Fornaro et al, 1996Fornaro et al, , 1999Meredith et al, 1995;Nagle et al, 1994). Integrins are transmembrane proteins, which form heterodimers of a and b subunits, thus forming unique receptors which bind specific extracellular matrix proteins (Giancotti and Ruoslahti, 1999;Yamada, 1997).…”
Section: Introductionmentioning
confidence: 98%
“…Limited understanding is available concerning the development and progression of prostate cancer despite its prevalence. Neoplastic changes are first apparent in prostatic intraepithelial neoplasia (PIN) and it is thought that PIN may be a precursor to prostate cancer [3][4][5][6][7][8][9]. PIN lesions are characterized by an attenuated basal lamina, enlarged nuclei, and an increased number of luminal type cells.…”
Section: Introductionmentioning
confidence: 99%
“…Laminin 5 is downregulated or lost in several squamous and epithelial carcinomas including the prostate [10,[21][22][23][24]. In our previous studies, we have found that the loss of laminin 5 and the α6β4 integrin (laminin receptor) was a characteristic feature accompanying the transition of normal prostate epithelial glands to PIN lesions to invasive prostate cancer [4,6,7].…”
Section: Introductionmentioning
confidence: 99%